A Comparative Clinical Study of Virechanakarma and KokilakshadiGhanvati in Amavata (Rheumatoid Arthritis) - Rao, Rajdip (International Journal of Pharmaceutical & Biological Archive, 2016)
Despite of amazing diagnostic machines and designer-crafted medicines, our society is suffering from preventable epidemics of heart disease, cancer, Rheumatoid Arthritis, other infectious illnesses. Ayurveda has taken the foremost place in the management of crippling diseases. Amavata is one of them. From the modern point of view, this disease looks similar toRheumatological disorders called Rheumatoid Arthritis. Aim & Objectives: To assess the clinical efficacy of VirechanKarma and KokilakshadiGhanvati in the management of Amavata(Rheumatoid Arthritis) Materials And Methods: 28 patients having Amavata and fulfilling the Criteria were selected (15 in Group A and 13 in Group B) in two groups irrespective of their sex, caste, religion from OPD & IPD of I.P.G.T. & R.A., Hospital, Gujarat Ayurved University, Jamnagar. Result: Group A provided better result than Group B. Statistical Analysis: It has been done by Wilcoxon test, Studentâ€™s â€œtâ€ test and Chi square test.